A data-driven approach to π0, η and η′ single and double Dalitz decays *Supported by the FPI scholarship BES-2012-055371 (S.G-S), the Secretaria d'Universitats i Recerca del Departament d'Economia i Coneixement de la Generalitat de Catalunya under grant 2014 SGR 1450, the Ministerio de Ciencia e Innovación under grant FPA2011-25948, the Ministerio de Economía y Competitividad under grants CICYT-FEDER-FPA 2014-55613-P and SEV-2012-0234, the Spanish Consolider-Ingenio 2010 Program CPAN (CSD2007-00042), and the European Commission under program FP7-INFRASTRUCTURES-2011-1 (283286) S.G-S also Received Support from the CAS President's International Fellowship Initiative for Young International Scientist (2017PM0031). (January 2018) - Escribano, Rafel; Gonzàlez-Solís, Sergi
Abstract: The dilepton invariant mass spectra and integrated branching ratios of the single and double Dalitz decays P → l + l − γ and P → l + l − l + l − ( P = π 0, η, η ′ ; l = e or μ ) are predicted by means of a data-driven approach based on the use of rational approximants applied to π 0, η and η ′ transition form factor experimental data in the space-like region.